Two successful elephant translocations in Kenya - Litoroh, Moses; Omondi, Patrick; Bitok, Elphas; Wambwa, Elizabeth (Pachyderm, 2001)
In the 7 years since the Kenya Wildlife Service made a decision to translocate rather than kill problem elephant the success rate of the transfer excercises has improved. Two excercises undertaken in 2000 were completed with no elephant deaths: in March 10 elephant (7 from Sweetwaters S and 3 from Lewa Conservancy) were moved from private game sanctuaries in Laikipia to Meru; and, in October 3 elephant were transferred to from Shimba Hills to Tsavo East NP. The 3 bulls moved in October were fitted with radio collars and subsequent monitoring has shown that thus far they have remained within 50 km of their release site